Review of research progress in sepsis-associated acute kidney injury - Nian, Wanning; Tao, Weichen; Zhang, Haiyi (Frontiers in Molecular Biosciences, 2025)
Sepsis-associated acute kidney injury (SAAKI) poses a significant challenge in critical care medicine, characterized by high morbidity and mortality rates and often leading to chronic kidney disease (CKD). This article provides a comprehensive overview of the pathophysiological mechanisms, diagnostic advancements, therapeutic strategies, and prognostic studies of SAAKI. In terms of pathophysiological mechanisms, research has shifted from the traditional renal ischemia-centric view to a multidimensional interplay involving microcirculatory disturbances, immune metabolic disorders, and programmed cell death. Regarding diagnosis, traditional Kidney Disease: Improving Global Outcomes (KDIGO) criteria exhibit limitations, whereas novel biomarkers and imaging techniques offer new avenues for early diagnosis. Therapeutic strategies encompass early intervention, hemodynamic management, renal replacement therapy, and targeted therapies; however, controversy persists regarding the optimal timing and methods of their initiation. Prognostic studies focus on the mechanisms underlying the transition from SAAKI to CKD and corresponding preventive strategies. Future research should bridge the gap between animal models and human pathology and explore the potential of multi-omics technologies and artificial intelligence in optimizing management.